Theoretical and methodological aspects of the formation of an effective forage base - Olga V Egorova (RUDN Journal of Economics, 2019)
This article is devoted to the organization of agricultural production of feed. Studied basic views on the definition of “fodder” and “fodder base”, and their relationship to agriculture. On the basis of the system approach the main factors influencing efficiency of system of agricultural production of forages for cattle are revealed. The criteria for increasing the efficiency of feed production in the process of structuring the formation of the forage base are substantiated. The analysis shows how the agricultural sector is not a closed system. The level of economic development of feed production and the formation of the feed base is determined not only by internal but also external factors, the organization of the correct interaction of which acts as a starting point for accelerating scientific and technological progress in the industry and increasing the level of development of agriculture.